Bilateral agenesis of arcuate fasciculus demonstrated by fiber tractography in congenital bilateral perisylvian syndrome - EKİNCİ, GAZANFER; AĞAN YILDIRIM, KADRİYE (ELSEVIER SCIENCE BV, 2015)
Congenital bilateral perisylvian syndrome (CBPS) is a type of cortical developmental abnormality associated with distinctive clinical and imaging features. Clinical spectrum of this syndrome is quite heterogeneous, With different degrees of neurological impairment in affected individuals. High-definition magnetic resonance imaging (MRI) has a great importance in revealing the presence of CBPS, but is limited in elucidating the heterogeneous clinical spectrum. The arcuate fasciculus (AF) is a prominent language tract in the perisylvian region interconnecting Broca and Wernicke areas, and has a high probability of being affected developmentally in CBPS. Herein, we report a case of CBPS with investigation of AF using diffusion tensor imaging (DTI) and fiber tractography in relation to clinical findings. We postulated that proven absence of AF on DTI and fiber tractography would correlate with a severe phenotype of CBPS. (C) 2014 The Japanese Society of Child Neurology. Published by Elsevier B.V. All rights reserved.
Keywords: Congenital bilateral perisylvian syndrome; Arcuate fasciculus; Fiber tractography